2017
DOI: 10.3847/1538-4357/aa8874
|View full text |Cite
|
Sign up to set email alerts
|

The Star Formation Main Sequence in the Hubble Space Telescope Frontier Fields

Abstract: We investigate the relation between star formation rate (SFR) and stellar mass (M), i.e. the Main Sequence (MS) relation of star-forming galaxies, at 1.3 ≤ z < 6 in the first four HST Frontier Fields, based on rest-frame UV observations. Gravitational lensing combined with deep HST observations allows us to extend the analysis of the MS down to log M/M ⊙ ∼ 7.5 at z 4 and log M/M ⊙ ∼ 8 at higher redshifts, a factor of ∼10 below most previous results. We perform an accurate simulation to take into account the ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
235
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(285 citation statements)
references
References 82 publications
(131 reference statements)
47
235
0
Order By: Relevance
“…Qualitatively, the evolution of the M * − SFR relation that we find in our models agrees with the observed evolution (Tasca et al 2015;Santini et al 2017), although the latter is derived for more massive galaxies. In particular, the specific SFR (SFR/M * ) increases with redshift, and galaxies have similar specific SFRs across the mass range at a given redshift.…”
Section: Trends Of Dwarf Galaxy Propertiessupporting
confidence: 86%
See 1 more Smart Citation
“…Qualitatively, the evolution of the M * − SFR relation that we find in our models agrees with the observed evolution (Tasca et al 2015;Santini et al 2017), although the latter is derived for more massive galaxies. In particular, the specific SFR (SFR/M * ) increases with redshift, and galaxies have similar specific SFRs across the mass range at a given redshift.…”
Section: Trends Of Dwarf Galaxy Propertiessupporting
confidence: 86%
“…In particular, the specific SFR (SFR/M * ) increases with redshift, and galaxies have similar specific SFRs across the mass range at a given redshift. Quantitatively, the specific SFR in the most massive galaxies in our models is lower by a factor of a few than the average observational result, both at z = 0 (Peng et al 2010) and at higher redshift (Tasca et al 2015;Santini et al 2017). The SFRs observed in low-mass galaxies agree very closely with our model results, however (figure 2, panel c).…”
Section: Trends Of Dwarf Galaxy Propertiessupporting
confidence: 83%
“…If we interpret our point at z ≈ 5.5 as a statistical fluctuation 1σ below a true value ≈ 0.35 as found by De Barros et al (2017), we confirm this shallower increase of the LAE fraction towards z ≈ 5 and z ≈ 6. This could indicate the stop of the evolution of the Lyα escape fraction, possibly related to the plateau evolution of the star formation main sequence at z ≈ 5-6 suggested by Speagle et al (2014) and Salmon et al (2015), and implying a constant stellar mass at a given M 1500 (see however, Santini et al 2017).…”
Section: The Redshift Evolution Of the Lae Fraction And Implications mentioning
confidence: 94%
“…We can see that the observations of Heinis et al (2014) and Bouwens et al (2012) differ from the EAGLE reference model by ≃ 0.5 − 1 dex. However, the Salmon et al (2015) and Santini et al (2017) observations are within ≃ 0 − 0.3 dex from the predictions. This behavior is found at all redshifts with the reference EAGLE model and observations having offset star formation rates from −0.2 to 1.0 dex depending on masses and redshifts.…”
Section: Eagle Vs Observationsmentioning
confidence: 57%
“…We note that these assumptions are motivated by observational studies but not necessarily stand neither for the real/observed nor the EAGLE+SKIRT simulated galaxies (in table 1 we sumarize the SED fitting assumptions used by different authors). We employ numerous wavelengths filters like GALEXF U V , GALEXNUV , SDSSu, SDSSg, SDSSr, SDSSi, SDSSz, TwoMassJ , TwoMassH , TwoMassKs, UKIDDSZ, UKIDDSY , UKIDDSJ , UKIDDSH, UKIDDSK, JohnsonU , JohnsonB , JohnsonV , JohnsonR, JohnsonI , JohnsonJ , JohnsonM , WISEW 1, WISEW 2, WISEW 3, WISEW 4, IRAS12, IRAS25, IRAS60, IRAS100, IRACI1, IRACI2, IRACI3, IRACI4, MIPS24, MIPS70, MIPS160, PACS70, PACS100, PACS160, SPIRE250, SPIRE350 and SPIRE500 in order to limit parameter degeneracies to the SED fitting procedure (Katsianis et al 2016;Santini et al 2017).…”
Section: Stellar Masses and Sfrs From The Eagle+skirt Datamentioning
confidence: 99%